2010
DOI: 10.1002/ejsp.713
|View full text |Cite
|
Sign up to set email alerts
|

Indirect influence and divergent thinking as a function of member status and task structure in small groups

Abstract: A laboratory experiment examined the effect of confederate status and task structure on group members' use of the confederate's problem solving strategies (private/indirect influence) and divergent thinking. Twenty-eight three-member, all-female groups, with an experimental confederate acting as one of the group members, solved an open-structured or closed-structured logic problem. The confederate, randomly assigned to be higher-, lower-, or of undesignated-status, presented a scripted but unique solution to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Moscovici, , 1985. When ingroup normative members are marginal in the group, it seems plausible that deviant ingroup full members acquire the ability to elicit divergent thinking whereby group members consider alternative arguments that validate the deviant position (Martin & Hewstone, 2008;Nemeth, 1986; see also Goodman, Alexander, Chizhik, Chizhik, & Eidelman, 2010). As a result, if a deviant member occupies a high-status role in the group others become more tolerant of the person (Abrams et al, 2008) and more accepting of his or her position (see Levine & Moreland, 1985;Levine et al, 2005).…”
Section: Group Processes and Intergroup Relations 19(5)mentioning
confidence: 99%
“…Moscovici, , 1985. When ingroup normative members are marginal in the group, it seems plausible that deviant ingroup full members acquire the ability to elicit divergent thinking whereby group members consider alternative arguments that validate the deviant position (Martin & Hewstone, 2008;Nemeth, 1986; see also Goodman, Alexander, Chizhik, Chizhik, & Eidelman, 2010). As a result, if a deviant member occupies a high-status role in the group others become more tolerant of the person (Abrams et al, 2008) and more accepting of his or her position (see Levine & Moreland, 1985;Levine et al, 2005).…”
Section: Group Processes and Intergroup Relations 19(5)mentioning
confidence: 99%
“…Based upon these findings, we propose that the specific framing of a group problem can establish a participatory environment where lower‐status group members are taken seriously. Specifically, research from our lab (Chizhik, Alexander, Chizhik, & Goodman, 2003; Goodman, Alexander, Chizhik, Chizhik, & Eidelman, 2009) suggests that altering the way in which a task or problem is framed and constrained shows promise as a simple, one‐shot intervention capable of producing a more democratic group environment in which lower‐status individuals have chances for meaningfully participating and overcoming their lower‐status position.…”
Section: Status Treatments In the Ongoing Classroom And Beyondmentioning
confidence: 99%
“…Using procedures similar to our previous research (Goodman et al, 2009), we asked groups comprised of two female participants and one female confederate to work on an open‐ or closed‐structured logic problem (i.e., seafood restaurant menu task) after assigning group members higher or lower status such that the confederate's status was opposite that of the two participants’ (in an additional condition, status was not manipulated). Again, participants were asked to rate the extent to which they and their groupmates possessed various ability characteristics (e.g., explaining things to others, keen observation, and being exact).…”
Section: Study 2: Preliminary Evidence For the Relationship Between Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of task, or how the embedded problem of a task is presented (Goodman, Alexander, Chizhik, Chizhik, & Eidelman, 2010), also plays a significant role on performance. Nouri, Erez, Rockstuhl, and Ang (as cited in Erez & Nouri, 2010) found that, compared to a well-defined and strong structure (i.e., with detailed instructions) task, an ill-defined and weak structure task is positively associated with originality of ideas.…”
Section: The Relationship Between Task Features and Performancementioning
confidence: 99%